2000
DOI: 10.1016/s0378-1097(00)00298-6
|View full text |Cite
|
Sign up to set email alerts
|

Retention of bacteria on a substratum surface with micro-patterned hydrophobicity

Abstract: Bacteria adhere to almost any surface, despite continuing arguments about the importance of physico-chemical properties of substratum surfaces, such as hydrophobicity and charge in biofilm formation. Nevertheless, in vivo biofilm formation on teeth and also on voice prostheses in laryngectomized patients is less on hydrophobic than on hydrophilic surfaces. With the aid of micro-patterned surfaces consisting of 10-Wm wide hydrophobic lines separated by 20-Wm wide hydrophilic spacings, we demonstrate here, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…The link between initial adhesion and biofilm detachment is due to the adhesive bond between the mature biofilm and the surface, where this adhesive force is governed by the same physicochemical forces that cause initial adhesion [127]. A study by Bos et al [128] concluded that substratum hydrophobicity is a major determinant of bacterial detachment under high shear forces. It is therefore clear that an understanding of bacterial-surface interactions may play an important role in biofouling detachment, and hence control.…”
Section: Discussionmentioning
confidence: 99%
“…The link between initial adhesion and biofilm detachment is due to the adhesive bond between the mature biofilm and the surface, where this adhesive force is governed by the same physicochemical forces that cause initial adhesion [127]. A study by Bos et al [128] concluded that substratum hydrophobicity is a major determinant of bacterial detachment under high shear forces. It is therefore clear that an understanding of bacterial-surface interactions may play an important role in biofouling detachment, and hence control.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that bacterial adhesion decreased with the increasing contact angle of the solid surfaces and the decreasing surface energy of the substrate surfaces 18,20,41,42) . Some research found that bacteria adhered to the hydrophobic materials could be more easily removed by an air-bubble jet 43,44) . It was also reported that there exists direct the relationship between the contact angle and the antibacterial property of various fluorideimplanted stainless steel 18,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adhesion is, thus, affected by surface properties (Litzler et al 2007;Schildhauer et al 2007) such as hydrophobicity (Schackenraad et al 1992;Bos et al 2000;Karakeçili and Gümü derelioglu 2002), hydrophilicity (Kiss et al 1996;Gomez-Suarez et al 2002), steric hindrance (Kuhl et al 1994;Rijnaarts et al 1999), and surface roughness (Medilanski et al 2002;Whitehead et al 2006). There is a positive correlation between protein adsorption and short-term bacterial attachment with surface property changes (Cunliffe et al 2003).…”
Section: Introductionmentioning
confidence: 99%